Instruments to identify elderly patients in the emergency department in need of geriatric care - Thiem, Ulrich; Heppner, Hans Jürgen; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2015)
The number of people with functional limitations, cognitive impairment and disability with unscheduled, unintended contact to emergency departments seeking acute medical care is increasing. With this, the problem of how to identify elderly people in need for acute geriatric care has evolved. The best solution to the problem would be to perform comprehensive geriatric assessment during the initial contact; however, comprehensive geriatric assessment is considered too complex and therefore not feasible for emergency departments. Instead, screening instruments have been developed and proposed. In this narrative review, selected screening instruments are discussed. The instrument best studied in various settings and countries is the Identification of Seniors At Risk (ISAR) screening tool which contains six simple questions that are easy to administer and can be assessed even in urgent situations. In recent years, several studies have examined the validity of ISAR in different European countries. Most of these studies, including one German study and a recent systematic review, confirmed the validity of ISAR. Unfortunately, evidence is conflicting, as some studies found only weak or even no association between ISAR and negative health outcomes. Other instruments have been investigated to a lesser extent and do not indicate obvious advantages over ISAR. Despite growing evidence in the field, there are still many uncertainties. Further research is needed to solve existing inconsistencies and to assess how elderly patients screened positive for acute geriatric care needs can best be managed further.
EVALuna2:10575